Wi-Fi: Spreading from the centre - Atkinson, John; Boateng, Ebenezer; Amoah, Gideon K. (Technical Centre for Agricultural and Rural Cooperation, 2008)
From a small initial investment of their own money, a group of volunteers in Ghana has managed to build a wireless network spanning 20 km. Local farmers and schoolchildren have already benefited from this very inventive system.